Aktualisasi Moderasi Beragama Pada Masyarakat Multi Etnis Di Kota Surabaya - Ficky Dewi Ixfina (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2006)
This study aims to understand how religious moderation is actualized in the social life of multiethnic communities in Surabaya City, the role of government and religious leaders in maintaining harmony between religious communities, and the influence of digitalization and social media on people's religious perspectives. This study uses a qualitative method with a phenomenological approach to explore people's experiences and meanings of religious moderation practices in everyday life. Data were obtained through in-depth interviews, field observations, and documentation, with informants selected purposively and developed through snowball sampling. Data analysis was carried out interactively using the Miles-Huberman model through the stages of data reduction, data presentation, and drawing conclusions and verification. The results show that religious moderation in Surabaya's multiethnic community grows contextually and practically, but requires strengthening digital literacy and ongoing collaboration between the government, religious leaders, and the community to remain relevant and adaptive amidst social and digital dynamics